An investigation of a catalytically-ignited autothermal reformer pre-heating system for hydrogen production for cell powered vehicle - Hassan, Zulkafli Bin (2008)
The platinum catalyst involved a very high· cost because ofthe platinum price it self. Preparation of platinum catalyst to an alumina support has been investigated in this study. The sample Pt/Ah03 catalyst was prepared with different platinum weight loading which is 1wt% and 3wt% by impregnation process. Hexachloroplatinic acid H2PtC16 and y-A1203 solutions were used in this preparation. The hydrazine (NH4) was added to reduce the chlorine ion from platinum. Catalyst characteristic was analysed using Fourier Transform Infrared (FTIR) spectroscopy and Scanning Electron Micrograph (SEM). Comparison with literature FTIR data indicated that platinum was dispersed into y-A1203. SEM micrograph show that crystallites structure of platinum was formed at y-A1203 surface. This research also to investigate the performance of catalytic combustion of hydrogen by using Pt/AI20 3 in different weight loading catalyst ranged from 0.06g to 0.2g in assisting the catalytic combustion of methane experimentally. 1wt% and 3wt% platinum catalyst was used to determine the performance of catalytic combustion of hydrogen. The behavior of hydrogen has been studied accordingly based on their auto ignition in room temperature and atmospheric pressure when contact with platinum with air in the range of lower and upper flammability limits. Sets of range from 72% to 97% fuel to air ratio were used for the experiment. The catalytic combustion of hydrogen was a complete combustion and could reach up to 450°C. The experiment held in vertical single bed reactor whereby the exit temperature of catalytic combustion of hydrogen was recorded for performance comparison.